Peripartum Ultrasound-Guided Drainage of Cystic Fetal Sacrococcygeal Teratoma for the Prevention of the Labor Dystocia: A Report of Two Cases - Stefanovic, Vedran; Halmesmäki, Erja (American Journal of Perinatology Reports, 2011)
Fetal sacrococcygeal teratoma (SCT) is the most common tumor in the neonatal period and is easily detected by modern ultrasound techniques, mostly during the second-trimester screening. It can cause significant fetal/neonatal morbidity and mortality due to its size, vascular loading, possible rupture, and labor dystocia. Mostly cystic teratomas have favorable prognosis, but if untreated in utero, they may rupture or cause labor obstruction. Cesarean delivery, especially with the vertical incision, increases significantly maternal morbidity due to the hemorrhage and the risk of the uterine rupture in the subsequent pregnancies. The authors report in details two SCT cases with uncomplicated vaginal delivery after peripartum ultrasound-guided drainage of the cystic teratoma. We conclude that the percutaneous emptying of the cystic SCT is an easy, encouraging, safe, and efficient procedure and enables normal vaginal delivery, thus avoiding labor dystocia and possible complications of the cesarean delivery and the risk of tumor rupture.
Keywords: Fetal sacrococcygeal teratoma; prenatal diagnosis; fetal surgery; prevention of dystocia; ultrasound